Annual reports in medicinal chemistry. Vol. 36 - Doherty, Annette M. (Annette Marian), 1961-; ScienceDirect eBooks ([Place of publication not identified] : Academic Press, 2001)
Annual Reports in Medicinal Chemistry provides timely and critical reviews of important topics in medicinal chemistry together with an emphasis on emerging topics in the biological sciences, which are expected to provide the basis for entirely new future therapies.
Online resource; title from publisher's Web site (ScienceDirect, viewed on June 18, 2012).
Includes bibliographical references and indexes.
Elsevier
Keywords: Pharmaceutical chemistry; Clinical chemistry; Clinical chemistry; Pharmaceutical chemistry; Electronic books